ANALISIS PENGARUH SUHU TERHADAP SENSITIVITAS SENSOR PADA HIDUNG ELEKTRONIK UNTUK KEMATANGAN BUAH KELAPA SAWIT - Dian Eka Rachmawati; Minarni Shiddiq (Komunikasi Fisika Indonesia, 2022)
Electronic noses have been developed for decades in many fields. Recently, electronic nose has been used in agriculture to detect the ripeness of fruits because fruits also produce volatile gas during ripening. Oil palm fresh fruit bunches (FFB) is the main source of crude palm oil, its quality depends on the ripeness levels of oil palm FFB. Therefore, electronic detections of oil palm FFB ripeness need to be developed. This study was aimed to investigate the effect of temperature variation on the sensitivity of gas sensors in an electronic nose designed for detecting the ripeness of oil palm FFB. The electronic nose used in this study consisted of 4 sensors which were TGS 2611, TGS 2620, TGS 813 and TGS 822. Samples were peeled fruitlets of ripe oil palm FFB which were heated to temperatures of 30°C, 45°C, and 60°C. Response of each sensor was represented as a trapezoid area of voltage versus time for convenience. The results showed that there was a significant difference in the output voltage of each sensor when the sample temperatures were varied. Fruitlets of oil palm FFB heated at 60°C resulted in higher trapezoid area which mean more volatile gas released.  Based on the resulted trapezoid area for each sensor. Sensors of TGS 2611 and TGS 822 are the most sensitive which have higher trapezoid area for the variation of the temperatures.